PENGARUH KUALITAS PELAYANAN DAN DISIPLIN KERJA TERHADAP KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - NOVA SIMAT (Journal of Management and Accounting (JMA), 2026)
This study aims to analyze the effect of Capability and Job Satisfaction on Employee Performance at the Office of the Office of Women's Empowerment and Child Protection, Sorong City. This study uses descriptive and correlation quantitative research methods. Data collection techniques used questionnaires and interviews with all employees of the Sorong City Office of Women's Empowerment and Child Protection as many as 30 respondents using the Saturated Sampling Technique. This study used the SPSS Version 20 application program for windows, the results of this study indicate that the variables Capability and Job Satisfaction on Employee Performance have a positive and significant effect).